Republic of Madagascar : 2019 Article IV Consultation and Sixth Review Under the Extended Credit Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Republic of Madagascar. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper presents 2019 Article IV Consultation with the Republic of Madagascar and its Sixth Review Under the Extended Credit Facility (ECF) Arrangement. Madagascar's performance under its economic program supported by the ECF arrangement has been broadly satisfactory with solid growth, moderate single digit inflation, and a robust external position. As a fragile, low-income country, Madagascar continues to face risks associated with weak implementation capacity, potential fiscal slippages, social fragility in a context of widespread poverty, and vulnerability to exogenous shocks including to terms of trade and natural disasters. Going forward, a commitment to strong policies and an ambitious agenda to complete outstanding structural reforms remains crucial to mitigate internal and external risks, strengthen macroeconomic stability, and achieve higher, sustainable, and inclusive growth. The authorities' economic reform agenda summarized in the Plan Emergence Madagascar aims to raise economic growth through increased public and private investment, strengthening human capital, and improving governance. Creating additional fiscal space by further improving revenue mobilization through a medium-term tax revenue strategy, containing lower priority spending, and enhancing investment implementation capacity is essential for scaling-up priority investment and social spending in education, health, and housing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet